Pengelolaan Dan Penyaluran Dana Zakat dalam Program yang Bekerjasama dengan Mitra di Baitul Maal Manfaat Surabaya - Yurina Dewi Andaru; Karjadi Mintaroem (Universitas Airlangga, 2019)
This research aimed to find out the way of management and distribution of zakat fund in Manfaat Mitra Mandiri (M3) program existed at Baitul Maal Manfaat Surabaya. The method used was descriptive method with case study. This research also used interview, documentation, and direct observation techniques. The results of the research showed that the management and distribution systems of zakah fund in this program were a co-operation with partners, and then the partners gave the fund to the party of Baitul Maal Manfaat Surabaya to manage. After mustahik has received loan assistance, she must make installment payments on a monthly basis, up to ten months from the time the loan was received. Mustahik would pay the payments and it would be given to the parties of Baitul Maal Manfaat Surabaya, and after that they collected it and gave it back to the partners that were suitable to the Manfaat Mitra Mandiri (M3) program.Keywords:Distribution, Zakah Fund, Baitul Maal, MustahikREFFERENCESAlmath, Muhammad Faiz. 1991. 1100 Hadits Terpilih:Sinar Ajaran Muhammad. Jakarta: Gema Insani. Al-Qur’an dan Terjemahannya Departemen Agama RI. 2001. Semarang: CV. Asy Syifa’. Arifin, Gus. 2016. Keutamaan Zakat, Infak, Sedekah : Dilengkapi dengan Tinauan salam Fikih 4 Mazhab. Jakarta: PT. Elex Media Komputindo. Indonesia Magnificence of Zakat bekerjasama dengan Pusat Ekonomi dan Bisnis Syariah Universitas Indonesia. 2009. Zakat dan Pembangunan : Era Baru Zakat Menuju Kesejahteraan Ummat. Cet. Ke-I. Ciputat: Indonesia Magnificence of Zakat. Kartika, Elsi. 2006. Pedoman Pengelolaan Zakat. Semarang: UNNES Press. Mardani. 2015. Fiqh Ekonomi Syariah Fiqh Muamalah. Cet. Ke-3. Jakarta: Prenadamedia Grup. Mursyidi. 2006. Akuntansi Zakat Kontemporer. Bandung: PT. Remaja Rosdakarya. Nurul Huda, dkk. 2012. Keuangan Publik Islam Pendekatan Teoritis dan Sejarah. Jakarta: Kencana.Qardawi, Yusuf. 2011. Hukum Zakat: Studi Komparatif Mengenai Status dan Filsafat Zakat Berdasarkan Qur’an dan Hadis. Bogor: Pustaka Litera Antar Nusa. Rasyid, H. Sulaiman. 1994. Fiqh Islam. Cet. Ke-27. Bandung: Sinar Baru Algensindo. Sugiyono. 2012. Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung: Alfabeta. Widodo, H G. Suseno Triyanto. 1997. Indikator Ekonomi Dasar dan Kebijaksanaan Perekonomian Indonesia. Jakarta: Kanisius Media.Yin, Robert K. 2015. Studi Kasus: Desain dan Metode. Depok: Raja Grafindo Persada.